Project-based learning on environmental change to enhance numeracy skills and environmental awareness to support SDGs 13 - Tari Anjani; Wiwit Artika; Rahmah Johar; Andi Ulfa Tenri Pada; M. Ali Sarong (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2025)
Numeracy skills and an environmental care attitude are essential competencies for environmental sustainability, yet both are currently low among students. This study aimed to: (1) analyze the enhancement of students' numeracy skills, (2) evaluate the improvement of their environmental care attitude through a project-based learning model, and (3) determine differences in these competencies based on gender.  A quantitative approach with a pretest-posttest control group experimental design was employed. The sample comprised 32 tenth-grade students selected via purposive sampling. The t-test analysis showed a significant difference between the experimental and control groups (Sig. 2−tailed<0.05), confirming the effectiveness of project-based learning (PjBL) in improving numeracy and environmental care attitude. Furthermore, significant gender differences were observed, males scored higher in numeracy, while females scored higher in environmental care attitude. These findings affirm the importance of integrating numeracy and environmental issues into learning as a tangible strategy to support SDG 13. The project-based learning model is effective in improving environmental data analysis skills and climate mitigation awareness. This model is recommended for fostering students who are critical thinkers and possess pro-environmental behavior.Abstrak. Kemampuan numerasi dan sikap peduli lingkungan merupakan dua kompetensi esensial dalam mendukung keberlanjutan lingkungan, namun keduanya masih rendah di kalangan siswa. Penelitian ini bertujuan untuk: (1) menganalisis peningkatan kemampuan numerasi siswa, (2) mengevaluasi peningkatan sikap peduli lingkungan melalui model pembelajaran berbasis proyek, dan (3) mengetahui perbedaan kompetensi tersebut berdasarkan gender. Penelitian ini menggunakan pendekatan kuantitatif dengan desain eksperimen pretest-posttest control group. Sampel penelitian terdiri atas 32 siswa kelas X SMA Negeri Modal Bangsa yang dipilih melalui purposive sampling. Instrumen penelitian berupa tes numerasi dan angket. Hasil analisis uji-t menunjukkan adanya perbedaan signifikan antara kelompok eksperimen dan kontrol (Sig. 2-tailed < 0,05), yang menegaskan efektivitas pembelajaran berbasis proyek (PjBL) dalam meningkatkan kemampuan numerasi dan sikap peduli lingkungan. Selain itu, ditemukan perbedaan signifikan berdasarkan gender, yaitu siswa laki-laki memperoleh skor rata-rata lebih tinggi pada kemampuan numerasi, sedangkan siswa perempuan memperoleh skor rata-rata lebih tinggi pada sikap peduli lingkungan. Temuan ini menegaskan pentingnya integrasi numerasi dan isu lingkungan dalam pembelajaran sebagai strategi nyata mendukung SDG 13. Pembelajaran berbasis proyek efektif meningkatkan kemampuan analisis data lingkungan dan kesadaran mitigasi iklim. Model ini direkomendasikan untuk membentuk peserta didik yang berpikir kritis dan berperilaku pro-lingkungan.